(untitled) (Theatrum historiae, 2007)
The issues of nationalism and confession in Bohemian medieval and Early Modern periods presented a significant history-forming element of a long-term nature. The author focuses on the period at the break of the 15th and 16th centuries characterized by significant changes in given field of interest. In regard to the perception of nationality, the temporary Bohemian establishment started to feel a threat to national interest from Germany (Holy Roman Empire, the Reich), despite the notion of a nation as a significant state-forming element is, at the same time, being determined in neighbouring Germany within the empire reform under Maximilian I. The author explains such an apparent discrepancy by the fact that in the Bohemian political atmosphere at the end of the 15th century, the Czech character of the establishment was pursued, Czech language became and official language and the Bohemian Kingdom was legally separated from the Reich (1486) by a corporative decision of domestic aristocracy. Domestic aristocracy started to observe a greater danger from the side of Hungarian aristocracy that was becoming more influential due to the transfer of royal court to Buda (German: Ofen), and due to the increased land ownership in Czech lands. This was one of the reasons why Moravian (1480) aristocracy, followed by the Bohemian noblemen (1500), approaches the formation of a precise definition of nobility, that time vastly formed by Czech families. Religious Conciliation in Kutná Hora (1485) represented a landmark in the development of domestic religious scene. This political agreement made it possible to separate political component from the confessional one. Consequently, a social standard prevailed in the establishment, where the social status and nationality of an aristocrat were preferred to the confession despite the confession was formally outlawed (such as Jednota bratrská = the Union of Brethern). This principle was considered fundamental in the creation of a so called “super-confessional Christianity”. The author applies the model on Vilém of Pernštejn (1437-1521), an aristocrat who used his wealth and exceptional political power in the country to form a significant precedent in terms of nationality and confession, fundamentally affecting contemporary social standards.